Skin Cancer Surveillance Behaviors Among Childhood Cancer Survivors. Issue 3 (29th October 2015) - Stapleton, Jerod L.; Tatum, Kristina L.; Devine, Katie A.; Stephens, Sue; Masterson, Margaret; Baig, Amna; Hudson, Shawna V.; Coups, Elliot J.
Abstract : The risk of developing skin cancer is elevated among childhood cancer survivors (CCS), particularly among those treated with radiation. This survey study examined the skin cancer surveillance behaviors of 94 CCS. Approximately 48% of CCS had ever conducted skin self‐examination (SSE) and 31% had ever received a physician skin examination. Rates of physician skin examination were 2.5 times higher among CCS treated with radiation compared to those without radiation. However, rates of SSEs did not differ based on treatment history. These findings highlight the need to promote skin cancer surveillance as an important aspect of CCS survivorship care.